Filled polycarbonate compositions having low thermal expansion
By using a combination of aromatic polyacylates, reinforcing fiber or metal oxide spherical fillers, PMMI copolymers and phosphate stabilizers in polyacylate materials, the processing stability problem of high-filling polyacylate materials under dual thermal strain pressure is solved, and the molecular weight is not reduced and processing stability is improved.
Patent Information
- Application Number
- JP2021557483
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-28
- Filing Date
- 2020-03-20
- Publication Date
- 2025-04-14
- Estimated Expiration
- 2040-03-20
AI Technical Summary
The prior art is difficult to maintain the molecular weight in high-filling polyacylates without reducing, especially in the case of dual pressures of thermal strain, which affects the processing stability of the material.
A thermoplastic composite material comprising aromatic polyacylates, reinforcing fibers or metal or metal loid oxide spherical fillers, PMMI copolymers and phosphate stabilizers is used. When the filler ratio is 35% to 60% and the PMMI copolymer ratio is greater than 0.1%, the composite material combines with a phosphate stabilizer to improve the processing stability of the material.
The processing stability of high-filling polyacylate materials under dual thermal strain pressure is significantly improved, the reduction of molecular weight is reduced, and the reliability of material processing at high temperatures is ensured.
Smart Images

Figure 0007661234000001 
Figure 0007661234000002 
Figure 0007661234000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoplastic composition comprising A) an aromatic polycarbonate and B) Ba) reinforcing fibres and / or Bb) spherical particles of oxides of metals or metalloids of the 3rd main group, the 4th main group and / or the 4th transition group.The present invention further relates to a layer arrangement comprising a substrate layer and a reflective layer which is different from the substrate layer and at least partially covers the substrate layer, the reflective layer at least partially reflecting light in the wavelength range from 380 nm to 750 nm, a lighting device comprising a light source and a reflector, the reflector being arranged such that at least a part of the light emitted by the light source is reflected by the reflector, and a method for producing a moulded article. [Background technology]
[0002] (J) Polycarbonate compositions are of interest for the manufacture of supports for optical elements, such as reflecting surfaces or lenses, since they can be processed by injection molding. In such applications, the dimensional stability of the parts is particularly important, so that the carefully developed optical properties of the system are not negated due to thermal expansion during operation.
[0003] The support material must have a low and ideally isotropic thermal expansion (coefficient of linear thermal expansion, CLTE), which can be achieved using spherical fillers.
[0004] A further class of fillers in highly filled polycarbonate systems are reinforcing fibers. They can be used to provide the material with additional advantageous mechanical properties. The thermal behavior should be such that there is reduced deformation in one or two dimensions. Applications for such reinforced polycarbonate systems are, inter alia, lightweight housings for electronic components.
[0005] Furthermore, the support material must exhibit good processing stability so that its advantageous properties are not diminished by the injection molding process.
[0006] Patent Document 1 discloses a thermoplastic molding having high surface quality, as well as a method for producing a thermoplastic molding material and a molding. The thermoplastic composition comprises A) 30.0 to 100.0 parts by weight of at least one aromatic polycarbonate, B) 0.0 to 50.0 parts by weight of a rubber-modified graft polymer and / or vinyl copolymer, C) 0.00 to 50.00 parts by weight of a polyester, D) 5.0 to 50.0 parts by weight of at least one inorganic filler having a particle morphology selected from the group including spherical / cubic, tubular / disk, and plate-like shapes, and E) 0.00 to 5.00 parts by weight of further conventional additives, where the parts by weight of components A) to E) total 100 parts by weight.
[0007] US Pat. No. 5,399,633 relates to the use of at least one PMMI copolymer to reduce the molecular weight loss of aromatic polycarbonates in talc-containing polycarbonate compositions during compounding. One composition claimed consists of A) at least 68% by weight of aromatic polycarbonate, B) 10% to 30% by weight of talc, C) 0.2% to 6% by weight of PMMI copolymer, and D) optionally one or more further additives selected from the group consisting of flame retardants, anti-drip agents, impact modifiers, fillers different from component B, antistatic agents, colorants, pigments, carbon black, lubricants and / or release agents, heat stabilizers, blend partners, compatibilizers, UV absorbers and / or IR absorbers. However, the use of phosphite stabilizers is not described therein.
[0008] US Pat. No. 5,399,633 relates to the use of at least one PMMI copolymer to reduce molecular weight loss of aromatic polycarbonates in polycarbonate compositions containing one or more oxides of metals or metalloids of the third, fourth and / or fourth transition groups during compounding. One composition claimed consists of A) at least 60% by weight of aromatic polycarbonate, B) 10% to 30% by weight of one or more oxides of metals or metalloids of the third or fourth main group or the fourth transition group, C) 0.2% to 6% by weight of PMMI copolymer, and D) optionally one or more further additives different from components B and C selected from the group consisting of flame retardants, anti-drip agents, impact modifiers, fillers, antistatic agents, colorants, pigments, carbon black, lubricants and / or release agents, heat stabilizers, blend partners, compatibilizers, UV and / or IR absorbers. Here too, the use of phosphite stabilizers is not described. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] International Publication No. 2013 / 079555 [Patent Document 2] International patent application having application number PCT / EP2018 / 084599 and a priority date of December 20, 2017 (now published as WO 2019 / 121253) [Patent Document 3] International patent application having application number PCT / EP2018 / 084543 and a priority date of December 20, 2017 (now published as WO 2019 / 121229) Summary of the Invention [Problem to be solved by the invention]
[0010] The object of the present invention is to provide thermoplastic molding materials with a high content of spherical fillers or reinforcing fibers (depending on the desired thermal expansion behavior) which exhibit as little molecular weight loss as possible even after two exposures to thermal stress (compounding and injection molding). This applies in particular to the injection molding melt temperatures, which are particularly high in the case of polycarbonates, in particular 280°C to 300°C, preferably 290°C to 300°C, optionally even 330°C to 350°C, which facilitate the processing of the highly filled molding materials. A further object of the present invention is to provide downstream products based on these molding materials and corresponding manufacturing methods. [Means for solving the problem]
[0011] This problem is solved according to the present invention by: A) an aromatic polycarbonate; B) Ba) reinforcing fibers, and / or Bb) spherical particles of oxides of metals or metalloids of the third, fourth and / or fourth transition groups, A thermoplastic composition comprising: The composition comprises: C) PMMI copolymer; and D) phosphite and / or phosphine stabilizers; Further comprising: Furthermore, the problem is solved by a thermoplastic composition in which the proportion of B) is from ≧35% by weight to ≦60% by weight and the proportion of C) is greater than 0.1% by weight, in each case relative to the total weight of the composition.
[0012] It may be a component of a layer arrangement comprising a substrate layer comprising such a composition and a reflective layer, different from the substrate layer and at least partially covering the substrate layer, the reflective layer at least partially reflecting light in the wavelength range from 380 nm to 750 nm. Such a layer arrangement may be a component of a lighting device comprising a light source and a reflector, the reflector being arranged such that at least a part of the light emitted by the light source is reflected by the reflector, the reflector comprising said layer arrangement. A manufacturing method according to claim 15 uses the composition according to the invention. Such a manufacturing method is used for producing a molded article by forming a thermoplastic composition under the action of heat into a molded article. Advantageous developments are contained in the dependent claims. They may be combined if desired, unless the contrary is evident from the context.
[0013] Surprisingly, it has been found that in polycarbonate compositions having a high content of spherical fillers and / or reinforcing fibers, the processing stability can be increased even during the injection molding step after compounding when a certain minimum content of PMMI copolymer in combination with a phosphorus-containing stabilizer selected from the group of phosphite stabilizers and / or phosphine stabilizers is present.
[0014] A criterion for good processing stability of a polycarbonate homopolymer may in particular be if the number-average molecular weight Mw of the polycarbonate is less than 5% lower compared to the starting state before compounding (to produce a filled molding material) but before injection molding, and at the same time less than 7% lower compared to the starting state after injection molding.
[0015] For example, in the case of polycarbonate copolymers, such as copolycarbonates based on the monomers bisphenol A and 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, the second criterion would be "less than 10% lower compared to the starting state prior to injection molding."
[0016] Ingredient A Component A) is at least one aromatic polycarbonate. It is therefore also possible to use mixtures as component A). For the purposes of the present invention, polycarbonate is either homopolycarbonate or copolycarbonate, and polycarbonate can be linear or branched as known. Polycarbonate is produced from dihydroxyaryl compounds, carbonic acid derivatives, and optionally chain terminators and branching agents as known.
[0017] Preferred dihydroxyaryl compounds are selected from at least one of the group consisting of 4,4'-dihydroxybiphenyl, 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 2,4-bis(4-hydroxyphenyl)-2-methylbutane, 1,1-bis(4-hydroxyphenyl)-p-diisopropylbenzene, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, dimethylbisphenol A, bis(3,5-dimethyl-4-hydroxyphenyl)methane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, bis(3,5-dimethyl-4-hydroxyphenyl)sulfone, 2,4-bis(3,5-dimethyl-4-hydroxyphenyl)-2-methylbutane, 1,1-bis(3,5-dimethyl-4-hydroxyphenyl)-p-diisopropylbenzene, and 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane.
[0018] Examples of suitable carbonic acid derivatives are phosgene or diphenyl carbonate. Suitable chain terminators that can be used in the preparation of the polycarbonates used according to the invention are monophenols. Suitable monophenols are, for example, phenol itself, alkylphenols such as cresol, p-tert-butylphenol, cumylphenol, and mixtures thereof. Suitable branching agents are trifunctional or tetrafunctional or higher compounds known in polycarbonate chemistry, in particular compounds having 3 or 4 or more phenolic OH groups.
[0019] The polycarbonates A) are preferably homopolycarbonates based on bisphenol A, homopolycarbonates based on 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, copolycarbonates based on the monomers bisphenol A and 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, or mixtures of at least two of the aforementioned polymers.
[0020] Component B According to the invention, the composition contains reinforcing fibers as component Ba and / or at least one oxide of a metal or metalloid of the third or fourth main group or of the fourth transition group as component Bb. Suitable reinforcing fibers are, for example, glass or carbon fibers or mixtures thereof. These fibers preferably have a cut length of ≧2 mm to ≦5 mm and / or a cross-sectional ratio of ≧1:1 to ≦2:1.
[0021] The oxide of metal or metalloid of the third or fourth main group or the fourth transition group can be used alone or in mixture.Preferably, titanium dioxide, silicon dioxide and / or aluminum oxide, particularly preferably titanium dioxide and / or silicon dioxide, very particularly preferably titanium dioxide is used without further oxide of metal or metalloid of the third or fourth main group or the fourth transition group, especially except for the titanium dioxide coating and / or the silicon dioxide coating.Therefore, component Bb is preferably selected from this above-mentioned limited group.
[0022] Component B is the sum of the proportions of components Ba and Bb. Component B may comprise Ba alone, Bb alone or a mixture of Ba and Bb. Component B is preferably present in the composition according to the invention in an amount of 36% by weight to 55% by weight, more preferably 37% by weight to 50% by weight, even more preferably 38% by weight to 45% by weight, particularly preferably 39% by weight to 40% by weight, in each case relative to the total composition.
[0023] The silicon dioxide is preferably naturally occurring or synthetically produced quartz or fused silica.
[0024] The particles used in the composition according to the invention have a spherical particle morphology.In the present invention, the term "spherical" should be understood to include not only the ideal spherical morphology, but also particles described by equal length axes oriented in space starting from a common origin, these axes defining the particle radius in all spatial directions, and each can have an axis length deviation of up to 20% (preferably up to 10%) from the ideal spherical state, independently of each other.
[0025] The quartz preferably has a median diameter d determined according to ISO 13320:2009 of 2 μm to 10 μm, more preferably 2.5 μm to 8.0 μm, even more preferably 3 μm to 5 μm. 50 wherein the maximum diameter d determined according to ISO 13320:2009 is correspondingly 6 μm to 34 μm, more preferably 6.5 μm to 25.0 μm, even more preferably 7 μm to 15 μm, particularly preferably 10 μm 95 is preferred.
[0026] The quartz preferably has a pore size of 0.4 m, as determined by nitrogen adsorption according to ISO 9277:2010. 2 / g~8.0m 2 / g, more preferably 2m 2 / g~6m 2 / g, particularly preferably 4.4m 2 / g~5.0m 2 / g BET specific surface area.
[0027] More preferred quartz contains no more than 3% by weight of secondary components, whereby it is preferred that the Al2O3 content is less than 2.0% by weight, the Fe2O3 content is less than 0.05% by weight, the (CaO+MgO) content is less than 0.1% by weight, and the (Na2O+K2O) content is less than 0.1% by weight, in each case relative to the total weight of quartz or silicate.
[0028] It is preferred to use quartz which has a pH, measured in aqueous suspension according to ISO 10390:2005, in the range of 6 to 9, more preferably 6.5 to 8.0.
[0029] The quartz preferably has an oil absorption according to DIN EN ISO 787-5:1995-10 of preferably 20 g / 100 g to 30 g / 100 g.
[0030] In a preferred embodiment, component Bb is selected from fine quartz flour produced by iron-free grinding and subsequent air classification from post-treated quartz sand.
[0031] It is particularly preferred to use fused silica, ie fused quartz, which is silicon dioxide that has been melted and resolidified, as component Bb.
[0032] Quartz or fused silica with a coating on the surface can be used, and it is preferred to use epoxy-modified silane compounds, polyurethane-modified silane compounds, and unmodified silane compounds, methylsiloxane and methacryloylsilane coatings, or a mixture of the above-mentioned silane compounds.Epoxysilane coatings are particularly preferred.Sizing of silicon dioxide is carried out by the general methods known to those skilled in the art.
[0033] However, it is preferred that the silicon dioxide used in the composition according to the invention is uncoated.
[0034] Suitable titanium dioxide is preferably produced by the chloride process, hydrophobized and specially post-treated, suitable for use in polycarbonates, for example the commercial product Kronos 2230 (Kronos Titan).
[0035] Possible surface modifications of titanium dioxide include inorganic and organic modifications. These surface modifications include, for example, surface modifications based on aluminum or polysiloxanes. Inorganic coatings may contain 0% to 5% by weight of silicon dioxide and / or aluminum oxide. Organic based modifications may contain 0% to 3% by weight of hydrophobic wetting agents.
[0036] The titanium dioxide preferably has an oil absorption, determined in accordance with DIN EN ISO 787-5:1995-10, of 12 g / 100 g (titanium dioxide) to 18 g / 100 g (titanium dioxide), more preferably 13 g / 100 g (titanium dioxide) to 17 g / 100 g (titanium dioxide), particularly preferably 13.5 g / 100 g (titanium dioxide) to 15.5 g / 100 g (titanium dioxide).
[0037] Particularly preferred is titanium dioxide stabilized with aluminum and / or silicon compounds and having a titanium dioxide content of at least 96.0% by weight, which has the standard designation R2 according to DIN EN ISO 591-1:2001-8, part 1. Such titanium dioxide is available under the trade names Kronos® 2233 and Kronos® 2230.
[0038] When aluminium oxide is used as component Bb, it preferably has a pH, measured in aqueous suspension according to ISO 10390: 2005, of 7.0 to 7.4. The aluminium oxide is preferably uncoated.
[0039] The amount specified for component Bb in each case is based on the total weight of the oxide used, including any coating / surface modification.
[0040] Preferably, as component B) are used Bb) particles having an average diameter d 50 and average diameter d between 10 μm and 15 μm 98and / or Ba) spherical quartz having a cut length of 2 mm or more and 5 mm or less and a cross-sectional ratio of 1 or more:1 to 2 or less:1.
[0041] Component C Component C is selected from PMMI copolymers. PMMI copolymers are thermoplastics that are partially imidized methacrylic polymers. PMMI copolymers are obtained in particular by reacting PMMA with methylamine in a reactor in dispersion or in the melt. A suitable method is described, for example, in DE-A-1077872. Imide structures are produced along the polymer chain and, depending on the extent of the reaction, methacrylic anhydride and free methacrylic acid functions are also formed. The proportion of imide functions in the copolymer determines its heat resistance. The extent of the reaction can be tailored.
[0042] The PMMI copolymer has methyl methacrylate units (MMA), methyl methacrylimide units (MMI), methyl methacrylic acid units (MMS) and methyl methacrylic anhydride units (MMAH). Preferably, at least 90% by weight, more preferably at least 95% by weight, based on the total weight of the PMMI copolymer, of the PMMI copolymer is selected from MMA units, MMI units, MMS units and MMAH units. It is particularly preferred when the PMMI copolymer consists of only these units.
[0043] The units and their proportions in the PMMI copolymer are, in particular, 1 It can be determined by H NMR spectroscopy on the basis of the unambiguous chemical shift of the R' signal. Since the signals of the acid and anhydride monomer units cannot be unambiguously assigned, it is recommended to consider these units collectively.
[0044] The PMMI copolymer preferably has a proportion of MMI of at least 30% by weight, preferably at least 35% by weight, more preferably from 35% to 96% by weight, particularly preferably from 36% to 95% by weight, based on the total weight of the PMMI copolymer.
[0045] The MMA content of the copolymer is preferably between 3% and 65% by weight, preferably between 4% and 60% by weight, particularly preferably between 4.0% and 55% by weight, based on the total weight of the PMMI copolymer.
[0046] The proportion of MMS and MMAH in total is preferably at most 15% by weight, more preferably at most 12% by weight, particularly preferably from 0.5% to 12% by weight, based on the total weight of the PMMI copolymer.
[0047] The acid number of the PMMI copolymer, determined according to DIN 53240-1:2013-06, is preferably from 15 mg KOH / g to 50 mg KOH / g, more preferably from 20 mg KOH / g to 45 mg KOH / g, even more preferably from 22 mg KOH / g to 42 mg KOH / g.
[0048] Very particularly preferred PMMI copolymers are those which are in each case based on the total weight of the PMMI copolymer: 1 It has an MMI proportion of 36.8 wt.-%, an MMA proportion of 51.7 wt.-%, and an MMS+MMAH proportion of 11.5 wt.-%, determined by H NMR spectroscopy, and an acid number of 22.5 mg KOH / g, determined in accordance with DIN 53240-1:2013-06.
[0049] Alternatively, very particularly preferred PMMI copolymers are those which are in each case based on the total weight of the PMMI copolymer: 1 It has an MMI proportion of 83.1% by weight, an MMA proportion of 13.6% by weight, and an MMS+MMAH proportion of 3.3% by weight, determined by H NMR spectroscopy, and an acid number of 22.5 mg KOH / g, determined in accordance with DIN 53240-1:2013-06.
[0050] Likewise alternatively, very particularly preferred PMMI copolymers are those which are in each case based on the total weight of the PMMI copolymer: 1It has an MMI proportion of 94.8% by weight, an MMA proportion of 4.6% by weight, and an MMS+MMAH proportion of 0.6% by weight, determined by H NMR spectroscopy, and an acid number of 41.5 mg KOH / g, determined in accordance with DIN 53240-1:2013-06.
[0051] Suitable PMMIs are available, for example, from Evonik Industries AG under the "PLEXIMID™" brand.
[0052] According to the invention, it is provided that the proportion of PMMI copolymer C) is greater than 0.1% by weight. Moreover, the proportion of PMMI copolymer C) is preferably less than or equal to 0.5% by weight relative to the total weight of the composition. The proportion of C) is preferably greater than or equal to 0.2% by weight and less than or equal to 0.5% by weight relative to the total weight of the composition.
[0053] It is preferred if the glass transition temperature of the PMMI copolymer C), determined according to DIN EN ISO 11357-2:2014-07 at a heating rate of 20° C. / min, is from ≧120° C. to ≦170° C., preferably from ≧130° C. to ≦150° C. The PMMI copolymers are therefore stable under processing conditions customary for polycarbonates, including high-temperature stable polycarbonate copolymers.
[0054] Component D The phosphite and / or phosphine stabilizers may be used alone or as a component of a mixture. It is preferred when D) is tris(2,4-di-tert-butylphenyl)phosphite (Irgafos® 168), bis(2,4-dicumylphenyl)pentaerythritol diphosphite (Doverphos® S-9228), bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite (ADK STAB PEP-36), triphenylphosphine or a mixture comprising at least one of the abovementioned compounds.
[0055] It is preferable if the proportion of D) is ≧0.01% and ≦0.5% by weight relative to the total weight of the composition, this content preferably being ≧0.04% and ≦0.1% by weight.
[0056] The compositions according to the invention may comprise, as component E, further customary additives such as flame retardants, anti-drip agents, impact modifiers, antistatic agents, colorants, pigments, carbon black, lubricants and / or release agents, blend partners, compatibilizers, UV absorbers, IR absorbers, etc.
[0057] In a further embodiment, the composition comprises spherical particles Bb) and has a coefficient of linear thermal expansion (CLTE) of ≧20 ppm / K to ≦50 ppm / K, determined according to DIN 53752:1980-12 and measured in the temperature range from 23° C. to 60° C. The CLTE value in the longitudinal direction of the specimen preferably does not deviate from the CLTE value in the transverse direction of the specimen by more than 4 ppm / K, more preferably by more than 3 ppm / K.
[0058] In a further embodiment, the composition comprises reinforcing fibers Ba) and has a coefficient of linear thermal expansion (CLTE) determined according to DIN 53752:1980-12 and measured in the specimen direction corresponding to the longitudinal direction of the fibers within a temperature range of 23° C. to 60° C. of ≧10 ppm / K to ≦30 ppm / K. Preference is given if the CLTE in the specimen direction corresponding to the longitudinal direction of the fibers is ≧50 ppm / K to ≦70 ppm / K.
[0059] In a further embodiment, the composition comprises from ≧55% to ≦65% by weight, preferably from 54.79% to 64.79% by weight, of A), from ≧35% to ≦45% by weight, of B), from ≧0.2% to ≦0.5% by weight, and from ≧0.01% to ≦0.1% by weight of D), relative to the total weight of the composition, the weight percentages totaling up to 100% by weight.
[0060] The composition preferably comprises, based on the total weight of the composition: A) from 55% to 65% by weight, preferably from 54.79% to 64.79% by weight, of a homopolycarbonate based on bisphenol A, a homopolycarbonate based on 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, a copolycarbonate based on the monomers bisphenol A and 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, or a mixture of at least two of the aforementioned polymers, B) ≥ 35% and ≤ 45% by weight, Bb) in each case with an average diameter d of ≥ 3 μm and ≤ 5 μm, determined in accordance with ISO 13320:2009 50 and average diameter d between 10 μm and 15 μm 98 and / or Ba) a glass fiber having a cut length of 2 mm or more and 5 mm or less and a cross-sectional ratio of 1 or more:1 to 2 or less:1; C) 0.2% by weight to 0.5% by weight of a PMMI copolymer having a glass transition temperature of ≧120° C. to ≦170° C., determined at a heating rate of 20° C. / min according to DIN EN ISO 11357-2:2014-07; D) 0.01% by weight or more and 0.1% by weight or less of tris(2,4-di-tert-butylphenyl)phosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, triphenylphosphine, or a mixture containing at least one of the above compounds; and wherein the weight percentages total up to 100% by weight. It is more preferred if no further components are present in addition to further additives selected from the group flame retardants, anti-drip agents, impact modifiers, antistatic agents, colorants, pigments, carbon black, lubricants and / or release agents, blend partners, compatibilizers, UV absorbers, IR absorbers. It is preferred if the composition according to the invention consists only of components A) to D) and optionally a release agent.
[0061] The invention likewise relates to a layer arrangement comprising a substrate layer and a reflective layer different from the substrate layer and at least partially covering the substrate layer, the reflective layer at least partially reflecting light in the wavelength range from 380 nm to 750 nm, the substrate layer comprising a composition according to the invention. This means that preferably partial regions of the substrate layer or even the entire substrate layer are produced from the composition according to the invention. It is preferred if the substrate layer consists exclusively of the composition according to the invention. Thus, the reflective layer reflects visible light, and light of other wavelengths (UV, IR) is not excluded. The substrate layer preferably comprises or is a composition according to the invention comprising spherical particles Bb). The substrate layer more preferably has a linear coefficient of thermal expansion (CLTE) determined according to DIN 53752:1980-12 of ≧20 ppm / K to ≦50 ppm / K. It is even more preferred if, in the base material layer, the CLTE value in the machine direction of the test piece for determining the CLTE value does not deviate from the CLTE value in the machine direction of the test piece by preferably more than 4 ppm / K, more preferably by not more than 3 ppm / K.
[0062] In one embodiment of the layer arrangement, the reflective layer is a metal layer. The metal layer may be, for example, an aluminum layer or a noble metal layer. The layer may be applied by a chemical process, in particular chemical vapor deposition (CVD) or electroplating, or by a physical process, in particular physical vapor deposition (PVD) or sputtering.
[0063] In a further embodiment of the layer arrangement, the reflective layer has a thickness of ≧10 nm to ≦100 nm, preferably ≧30 nm to ≦80 nm.
[0064] The layer arrangement may be flat and therefore function as a simple mirror. In further embodiments, however, the layer arrangement is not flat. The layer arrangement may then function as a converging or diverging mirror. The layer arrangement may, for example, be in the form of a paraboloid of revolution.
[0065] The invention further provides a lighting device comprising a light source and a reflector, the reflector being arranged such that at least a part of the light emitted by the light source is reflected by the reflector, the reflector comprising a layer arrangement according to the invention. An example of such a lighting device is a headlight, such as is used as a front light in a motor vehicle.
[0066] The invention further relates to a method for producing a molded article by molding a thermoplastic composition under the action of heat to obtain a molded article, wherein the thermoplastic composition is a composition according to the invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS EXAMPLES
[0067] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited thereto.
[0068] polymer: A1:19cm 3 The polycarbonate is a commercial polycarbonate based on bisphenol A (Makrolon™ 2408 from Covestro Deutschland AG) with an MVR of 100° C. / 10 min (300° C. / 1.2 kg, ISO 1133-1:2011) and a softening temperature of 145° C. (VST / B 120; ISO 306:2013). The molecular weight Mw was approximately 23887 g / mol.
[0069] A2:18cm 3 The polycarbonate is a commercial copolycarbonate (Apec™ 1895 from Covestro Deutschland AG) based on bisphenol A and bisphenol TMC with an MVR of 100° C. / 10 min (330° C. / 2.16 kg, ISO 1133-1:2011) and a softening temperature of 183° C. (VST / B 120; ISO 306:2013). The molecular weight Mw was approximately 27855 g / mol.
[0070] Filler: B1: Amosil FW600(D 50= 4 μm, D 98 = 13 μm, uncoated) from Quarzwerke GmbH, 50226 Frechen, Germany. 10 / D 90 Ratio and determined according to DIN ISO 9277 (DIN-ISO 9277:2014-01), approx. 6 m 2 / g specific surface area.
[0071] B2: Glass fiber manufactured by Nitto Boseki Co., Ltd. (2-4-1 Kojimachi, Chiyoda-ku, Tokyo, 102-8489, Japan) available under the trade name CSG 3PA-830. This is a flat glass fiber having a cut length of 3 mm and a cross-sectional ratio of 1.4.
[0072] Stabilizers: C1: a commercial copolymer based on polymethacryloylmethylimide (Pleximid™ 8803) with a softening temperature of 130° C. (VST / B 50; ISO 306:2013).
[0073] C2: a commercial copolymer based on polymethacryloylmethylimide (Pleximid™ TT50) with a softening temperature of 150° C. (VST / B 50; ISO 306:2013).
[0074] D1: A phosphite from Adeka available under the trade name ADK-Stab-Pep36 (CAS number 80693-00-1; bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite).
[0075] D2: Triphenylphosphine (CAS number 603-35-0) manufactured by BASF.
[0076] D3: Stabilizer mixture from BASF (Ludwigshafen) sold under the trade name Irganox B900 (80% Irgafos 168; see D4 + 20% Irganox 1076; phenolic antioxidant; CAS number 2082-79-3).
[0077] D4: A phosphite available under the trade name Irgafos 168 from BASF (CAS number 31570-04-4).
[0078] D5: A phosphite available under the trade name Doverphos S9228 from Dover Chemical Corporation (CAS number 154862-43-8).
[0079] Release agent: E1: PETS (pentaerythritol tetrastearate).
[0080] Manufacturing conditions: Method A: BUSS kneader, melt temperature: 280°C-300°C, speed: 350 rpm, throughput: 75 kg / h, torque: 30%, addition of filler via side extruder.
[0081] Method B: ZE 25 AX 40D-UTX twin-screw extruder from Berstorff, extruder melt temperature: 300 °C (320 °C for polymer A2), extruder speed: 225 rpm, throughput: 20 kg / h, torque: 50%-60%, addition of filler via the lateral extruder in housing 5 (of 9).
[0082] procedure: The preparation of the polycarbonate compositions was carried out using either a BUSS kneader (Method A) or a twin-screw extruder (Method B). Depending on the equipment, the processing temperature was 225 min. -1 Or 350 minutes -1The temperature was between 280° C. and 300° C. at a speed of 100° C. Via the side extruder the fillers used were fed and via the main feed the powder premix containing the polycarbonate and all further additives was added.
[0083] After the granules had been thoroughly dried, test specimens were produced by injection molding at melt processing temperatures of 290°C to 330°C and, for the Apec™-containing molding materials, 310°C to 350°C.
[0084] The CLTE values were determined by thermomechanical analysis (TMA) according to DIN 53752:1980-12 in test specimens with dimensions 10 mm x 10 mm x 4 mm in the range between room temperature and 60°C.
[0085] Molecular weights Mw were determined as follows: gel permeation chromatography calibrated against bisphenol A polycarbonate standards using dichloromethane as eluent. Calibration with linear polycarbonates (formed from bisphenol A and phosgene) of known molar mass distribution from PSS Polymer Standards Service GmbH (Germany), calibration according to method 2301-0257502-09D (2009, German) from Currenta GmbH & Co. OHG (Leverkusen). Eluent is dichloromethane. Column combination of crosslinked styrene-divinylbenzene resin. Diameter of analytical column: 7.5 mm; length: 300 mm. Particle size of column material: 3 μm-20 μm. Concentration of solution: 0.2 wt.%. Flow rate: 1.0 ml / min, temperature of solution: 30° C. Injection volume: 100 μl. Detection by UV detector.
[0086] The reported compositions are numbered consecutively: "V" indicates a comparative example and "E" indicates an example according to the invention.
[0087] Compounding by Method A with Phosphite / PMMI and subsequent injection molding experiments:
[0088] [Table 1]
[0089] From Table 1, it is clear that, at first, the molecular weight of the polycarbonate does not decrease significantly in the compounding process even if the content of D1 is increased (compositions 1 to 3). However, when the content of component D1 is more than 0.15%, there is no longer a significant difference. The omission of D2 as a processing stabilizer has no effect on the molecular weight (see V-3 / V-4). The addition of C1 reduces the molecular weight loss during compounding (see E-5 and V-2). By increasing the C1 content, the amount of phosphite can be further reduced (see E-6 and V-1). The use of another conventional processing stabilizer (D3) shows a much larger molecular weight loss (see V-7 and V-1 and V-8 and V-3).
[0090] With regard to processing stability in downstream processes (injection molding), the differences are even more clear. Thus, composition E-6, which contains both phosphite and PMMI, is significantly more stable against molecular weight degradation than composition V-3, which contains only phosphite. Stability is demonstrated over the very wide temperature range associated with this material (higher filler content requires higher melt temperatures to ensure flow).
[0091] Thus, these results indicate a synergistic effect between the phosphite and PMMI.
[0092] Method B compounding with Phosphite / PMMI and subsequent injection molding experiments:
[0093] [Table 2]
[0094] From the data in Table 2, it is clear that there is a synergistic effect between phosphite / phosphine and PMMI in terms of processing stabilization. This is true for a series of different phosphorus-based heat stabilizers (D4 shows the highest effect, judged by the molecular weight of the active phosphorus species). The difference is small for C1 at a content of 0.2 wt.%, but it can be seen that the absence of PMMI in particular causes a significant deterioration of ΔMw from 5.9% to 11.3% (see, for example, V-13 vs. E-9). Comparing the molecular weight after extrusion, it becomes clear that the compositions containing both phosphite and PMMI suffer little significant damage compared to compositions V-13 and V-14. Thus, even though the percentage reduction in Mw is similar for V-14, the final value at each processing temperature is lower than for the compositions of the invention. Moreover, increasing the phosphite content (V-15) interestingly causes a significant deterioration compared to V-13.
[0095] Investigating the effect of PMMI concentration:
[0096] [Table 3]
[0097] From the data in Table 3, it is clear that increasing the concentration of C1 / C2 leads to a significant improvement in terms of processing stability (ΔMw). At a PMMI content of 0.5 wt%, the molecular weight of the polycarbonate compound was only reduced by 1% (the optimum upper limit is 0.5 wt%). This effect is also evident when C2 is used in the E-18 example.
[0098] Effect of filler content: Addition of further fillers (glass fibres, 30%-50% SiO2); Production by method B:
[0099] [Table 4]
[0100] Effect on copolycarbonates:
[0101] [Table 5]
[0102] The effect is equally clear in A2 (Apec™): increasing the content of stabilizer D1 shows only a slight improvement in the molecular weight loss at a processing temperature of 350° C. (see V-31 and V-30), but said loss is still significantly higher than in E-29.
Claims
1. A) an aromatic polycarbonate; B) Ba) reinforcing fibers, and / or Bb) spherical particles of oxides of metals or metalloids of Groups 13, 14 and / or 4; A thermoplastic composition comprising: The composition comprises: C) a PMMI copolymer; and D) a phosphite stabilizer and / or a phosphine stabilizer; Further comprising: said PMMI copolymer having a MMI proportion of at least 30% by weight, relative to the total weight of said PMMI copolymer, an MMA content of 3% to 65% by weight, relative to the total weight of said PMMI copolymer, and a proportion of MMS and MMAH in total of up to 15% by weight, relative to the total weight of said PMMI copolymer, moreover, The composition comprises, based on the total weight of the composition: 55% by weight or more and 65% by weight or less of A); 35% by weight or more and 45% by weight or less of B); C) in an amount of 0.2% by weight or more and 0.5% by weight or less; D) from 0.01% by weight to 0.1% by weight; and the total of said weight percentages is equal to or less than 100 weight percent. A thermoplastic composition comprising:
2. 2. The composition according to claim 1, wherein the aromatic polycarbonate A) is a homopolycarbonate based on bisphenol A, a homopolycarbonate based on 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, a copolycarbonate based on the monomers bisphenol A and 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, or a mixture of at least two of the aforementioned polymers.
3. Component B) is used Bb) having an average diameter d 50 and an average diameter d of 10 μm or more and 15 μm or less 98 and / or Ba) spherical quartz having a cut length of 2 mm or more to 5 mm or less and a cross-sectional ratio of 1 or more:1 to 2 or less:
1. The composition according to claim 1 or 2.
4. The composition according to any one of claims 1 to 3, further comprising C) in an amount of 0.5% by weight or less relative to the total weight of the composition.
5. 5. The composition according to claim 1 , wherein the glass transition temperature of the PMMI copolymer C), determined according to DIN EN ISO 11357-2:2014-07 at a heating rate of 20° C. / min, is ≧120° C. and ≦170° C.
6. The composition of any one of claims 1 to 5, wherein D) is tris(2,4-di-tert-butylphenyl)phosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, triphenylphosphine, or a mixture comprising at least one of the above compounds.
7. 7. The composition according to claim 1, wherein the proportion of D) is from 0.01% to 0.5% by weight relative to the total weight of the composition.
8. The composition according to any one of claims 1 to 7, comprising the spherical particles Bb) and having a coefficient of linear thermal expansion (CLTE) determined according to DIN 53752:19080-12 and measured in the temperature range from 23 ° C to 60 ° C of ≧ 20 ppm / K to ≦ 50 ppm / K.
9. A layer arrangement comprising a substrate layer and a reflective layer different from the substrate layer and at least partially covering the substrate layer, the reflective layer at least partially reflecting light in a wavelength range of 380 nm to 750 nm, A layer arrangement, characterized in that the substrate layer comprises a composition according to any one of claims 1 to 8.
10. 10. The layer arrangement according to claim 9, wherein the reflective layer is a metal layer.
11. 11. The layer arrangement according to claim 9 or 10, wherein the reflective layer has a thickness of ≧10 nm to ≦100 nm.
12. The layer arrangement according to any one of claims 9 to 11, wherein the layer arrangement is not flat.
13. 1. An illumination device comprising a light source and a reflector, the reflector being arranged such that at least a portion of light emitted by the light source is reflected by the reflector, A lighting device, characterized in that the reflector comprises a layer arrangement according to any one of claims 9 to 12.
14. A method for producing a molded article by molding a thermoplastic composition under the action of heat to obtain a molded article, characterized in that said thermoplastic composition is a composition according to any one of claims 1 to 8.
Citation Information
Patent Citations
Scratch-resistant polycarbonate compositions having good thermal stability
CN109476906A
Blend of imide polymer
JP1998158529A
(Co)polycarbonate with improved optical properties
JP2012521447A
Filled polycarbonate composition with improved flow and high stiffness
JP2017536460A
Polycarbonate resin composition
JP2018159004A